Braj B. Kachru's scholarly publications: A bibliography. Issue 1 (9th July 2019) - Bolton, Kingsley; Davis, Daniel R.; Sridhar, S. N.
Abstract: Although best known for his work on world Englishes, Braj Kachru was a truly original thinker, whose academic writings included influential publications on English linguistics, Indian languages, but much else besides, including applied linguistics, bilingualism and multilingualism, code‐mixing and switching, cross‐cultural communication, language policy, linguistic variation, literary creativity, sociolinguistics, and the politics of language. Braj B. Kachru was a renaissance scholar of immense stature, whose work brought together Indian and English linguistics with the cultural perspectives of both Asia and the West, and inspired scholars worldwide to adopt fresh perspectives on so many language issues.